2008
DOI: 10.2478/s11535-008-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of fluorescent singlet oxygen probes in plant leaves

Abstract: Four fluorescent singlet oxygen sensors: DanePy, its oxalate salt, Singlet Oxygen Sensor Green and MVP, were infiltrated into tobacco leaves and tested for toxicity, subcellular localization, light sensitivity and capacity to trap the singlet oxygen produced in photoinhibition. For reference, a broad sensitivity free radical probe, TEMPO-9-AC, was also included. Photochemical yield was approximately 15% and 10% inhibited by Singlet Oxygen Sensor Green and MVP, respectively, but was not significantly affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 47 publications
4
51
0
1
Order By: Relevance
“…4C, top row). Nuclear localization of SOSG was previously reported for mesophyll cells (Hideg, 2008). Although the signal in the nucleus was variable in some cases, it could clearly be detected in Figure 4.…”
Section: Stress-induced Accumulation Of Singlet Oxygen In the Dark Ansupporting
confidence: 71%
“…4C, top row). Nuclear localization of SOSG was previously reported for mesophyll cells (Hideg, 2008). Although the signal in the nucleus was variable in some cases, it could clearly be detected in Figure 4.…”
Section: Stress-induced Accumulation Of Singlet Oxygen In the Dark Ansupporting
confidence: 71%
“…A disadvantage of SOSG is that when illuminated with wavelengths below 600 nm, the fluorescence yield of SOSG increases similarly as during exposure to 1 O 2 ( Fig. 3; [92,109]). Furthermore, the reaction product of SOSG and 1 O 2 sensitizes 1 O 2 production [112].…”
Section: Dyesmentioning
confidence: 99%
“…Both imidazole and RNO are commercially available. According to the manufacturer's data, SOSG is cell-impermeable, but a study with tobacco leaves showed that a pinhole administration of SOSG to tobacco leaves leads to preferential association of the dye with the nuclei of epidermal cells [109]. Gollmer et al [110] showed that SOSG is also able to penetrate into human cells; therefore SOSG can be used in confocal microscopy [111].…”
Section: Dyesmentioning
confidence: 99%
See 2 more Smart Citations